A comparative study on Poisson control charts. Issue 3 (3rd May 2020) - Alevizakos, Vasileios; Koukouvinos, Christos
ABSTRACT: In many real applications, the quality characteristics of interest may be in the form of attribute counts which are often modeled by a Poisson distribution. For the monitoring of such data, many different control charts have been developed. In this article, we compare the performance of several widely used Poisson control charts in terms of the average run-length. Based on the comparison study, some recommendations are made in order to choose the best-performing control chart under different situations. Moreover, we apply these charts in real data relating to the airplane accidents.